Clear Aligners Versus Fixed Appliances In Malocclusion Treatment: A Systematic Review Of Efficacy And Patient Satisfaction (The Review of Diabetic Studies, 2025)
Background: Orthodontic treatment traditionally relied on fixed appliances, but the rise of clear aligners has introduced an aesthetic and comfortable alternative. Understanding their relative efficacy and patient-reported outcomes is essential for evidence-based decision-making.Objectives: This systematic review aimed to compare the clinical effectiveness, long-term stability, patient satisfaction, and periodontal outcomes of clear aligners versus fixed appliances in malocclusion treatment.Methods: The review adhered to PRISMA 2020 guidelines. Databases including PubMed, Scopus, Web of Science, Embase, and Google Scholar were searched from 2010 to 2024. Eligible studies involved human subjects undergoing treatment with either clear aligners or fixed appliances, with outcomes including treatment efficacy, patient-reported satisfaction, periodontal health, and long-term stability. Data extraction and risk of bias assessment were performed independently by two reviewers.Results: Fourteen studies met inclusion criteria. Clear aligners demonstrated comparable treatment effectiveness to fixed appliances in mild-to-moderate malocclusions, though fixed appliances retained superiority in complex movements such as torque and rotations. Aligners were consistently associated with greater comfort, reduced pain, higher patient satisfaction, and improved oral health-related quality of life. Periodontal outcomes favored aligners due to easier oral hygiene maintenance, while compliance and acceptance were higher among aligner patients. Long-term outcomes showed similar stability between both modalities, although high-quality randomized controlled trials remain limited.Conclusions: Clear aligners represent a clinically effective and patient-preferred alternative to fixed appliances, particularly in cases of mild-to-moderate malocclusion. While aligners offer advantages in comfort, satisfaction, and periodontal health, fixed appliances maintain biomechanical advantages in complex cases. Careful case selection remains critical, and further large-scale, long-term trials are needed to strengthen the evidence base.